Kerjasama Dinas Perhubungan Dan Dinas Sosial Dalam Pengadaan Fasilitas Transportasi Publik Darat (TRANSJAKARTA) Bagi Penyandang Disabilitas Di Provinsi Dki Jakarta - Tria Nurwara Dewi (Jurnal Administrasi Publik, 2016)
Abstract:Cooperation between the Department of Transportation and Departmen of Social Welfare in the Procurement Facility for Land Public Transportation (Transjakarta) for Persons with Disabilities in DKI Jakarta. DKI Jakarta is know as the busiest city, so that the society with high degree of mobility needs transportation services, person with disabilities are not expection. Transportation which has been providing facilities for person with disabilities of Transjakarta. The purpose of this study is to investigate and describe the forms of cooperation of department, the actors involved in the procurement of Transjakarta for disabilities, the result of the cooperation, supporting and inhibiting factors of cooperation of Department of Transportation and Department of Social Welare. Based on the result o the study, it show thet the procurement facilities of land public transportation (Transjakarta) for person with disabilities in Jakarta is already performing well. Department of Transportation, Department of Social Welfare and SMEC Local People Global Experience Australia Aid have been carrying out the rule nicely. Generating a Regulation No 10 o 2011 on the Protection o Person with Disabilities and also improving the inrastruktur facilities of Busway. Factors advocates there are sanctions for agencies which intentionally do not provide or facilitate people with a disabilitieswho werw found in regulation. Factors barrier the lack of awareness of the community and Transjakarta officer will needs priority for persons with disabilities, and the absence of the MOU that stengthen cooperation was conducted office Department of Transportation and Department Social Welfare.Â  Therefore, the MOU that need to be made strengthen their relations cooperation between the department. Keywords: Cooperation, Transjakarta, Disabilities, DKI Jakarta Abstrak: Kerjasama Dinas Perhubungan dan Dinas Sosial dalam Pengadaan Fasilitas Transportasi Publik Darat (Transjakarta) bagi Penyandang Disabilitas di Provinsi DKI Jakarta.Provinsi DKI Jakarta sebagai kota sibuk sehingga mobilitas masyarakatnya yang tinggi membutuhkan pelayanan transportasi, tidak terkecuali penyandang disabilitas. transportasi yang telah menyediaakan fasilitas bagi disabilitas adalah Transjakarta. Tujuan dari penelitian ini adalah untuk mengetahui dan mendeskripsikan bentuk kerjasama, aktor yang terlibat dalam pengadaan fasilitas Transjakarta bagi penyandang disabilitas, hasil kerjasama, faktor pendukung dan penghambat kerjasama Dinas Perhubungan dan Dinas Sosial. Hasil penelitian ini menunjukkan dalam pengadaan fasilitas transportasi publik darat (Transjakarta) bagi penyandang disabilitas di Provinsi DKI Jakarta sudah terlaksana dengan baik. Dinas Perhubungan, Dinas Sosial, dan SMEC Local People Global Experience Australia Aid sudah melaksanakan peran dengan baik. Serta, menghasilkan Peraturan Daerah DKI Jakarta Nomor 10 Tahun 2011 tentang Perlindungan Penyandang Disabilitas, melakukan perbaikan fasilitas sarana dan prasarana pada halte serta Busway.Faktor pendukungterdapat sanksi bagi instansi yang dengan sengaja tidak menyediakan atau memfasilitasi penyandang disabilitas yang terdapat di dalam Perda. Faktor penghambat yakni kurangnya kesadaran masyarakat dan petugas Transjakarta akan kebutuhan prioritas bagi disabilitas, serta belum adanya MOU yang menguatkan kerjasama yang dilakukan Dinas Perhubungan dan Dinas Sosial. Maka dari itu, perlu dibuat MOU yang menguatkan hubungan kerjasama antar dinas tersebut. Â  Kata kunci: Kerjasama, Transjakarta, Disabilitas, DKI Jakarta